Reliability of two difficulty indexes in predicting the surgical extraction difficulty of impacted mandibular third molars - Albayati Mohammed T.; Bede Salwan Y. (EDP Sciences, 2023)
Introduction: The aim of this study was to compare the reliability and the agreement of the Pederson and Pernambuco difficulty indexes in predicting the surgical extraction difficulty of the impacted mandibular third molars. Materials and methods: A prospective observational cohort study was conducted on 83 patients who had undergone surgical removal of impacted mandibular third molar. The difficulty of extraction was determined preoperatively according to the total scores obtained from the Pederson and Pernambuco difficulty indexes, the operative difficulty was determined by the surgical technique and the duration of extraction. The accuracy of prediction of the surgical difficulty and the degree of agreement of the two indexes were calculated. Results: The accuracy of Pederson and Pernambuco indexes in predicting the operative difficulty measured by duration of surgery was 36.1% and 55.4% respectively, and with operative difficulty measured by the technique was 21.7% and 37.3% respectively with statistically significant differences. The agreement between the 2 indexes was poor. Conclusion: Both indexes were limited in predicting the surgical difficulty of impacted mandibular third molars although the Pernambuco index was better than the Pederson index and the agreement between the two indexes was poor.